2020
DOI: 10.1080/14616696.2020.1823010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on gender inequality in the labor market and gender-role attitudes

Abstract: COVID-19 and ensuing changes in mobility have altered employment relations for millions of people across the globe. Emerging evidence shows that women may be more severely affected by this change. The pandemic, however, may have an impact beyond the immediate restructuring of employment and shift gender-role attitudes within households as a result of changes in the division of household labor. We analyze a representative sample of respondents in the U.S., Germany, and Singapore and show that transitions to une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
203
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(235 citation statements)
references
References 30 publications
20
203
2
10
Order By: Relevance
“…It is noteworthy that, within the descriptive results, the percentage of women is higher than men for unemployed, furloughed, on leave (other reasons), or teleworking individuals. These data are consistent with the literature that has studied the pandemic’s impact on the employment situation of men and women [ 39 ]. Also worth mentioning is the large percentage of people with a high level of education among those who are teleworking since the outbreak of the pandemic, this also being corroborated by the literature on the subject [ 33 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that, within the descriptive results, the percentage of women is higher than men for unemployed, furloughed, on leave (other reasons), or teleworking individuals. These data are consistent with the literature that has studied the pandemic’s impact on the employment situation of men and women [ 39 ]. Also worth mentioning is the large percentage of people with a high level of education among those who are teleworking since the outbreak of the pandemic, this also being corroborated by the literature on the subject [ 33 ].…”
Section: Resultssupporting
confidence: 92%
“…In addition, ref. [ 39 ] affirm that women will be more affected by job changes with a greater probability of moving towards either teleworking, a reduction in working hours or ultimately unemployment. These results suggest that the economic crisis prompted by the pandemic has proved especially detrimental to women, as opposed to the Great Recession, which hit men to a greater extent [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A cross-cultural study based on data from the U.S.A., Germany, and Singapore examined consequences of the pandemic for unemployment, underemployment, transitions to working from home, and for gender-role attitudes. The study indicated that compared to men, women were more likely to work from home, reduce their working hours, and become unemployed in the aftermath of the pandemic, and that this was mainly due to their pre-pandemic labor market precariousness (Reichelt et al 2020).…”
Section: Social Inequalitiesmentioning
confidence: 98%
“…However, there is fairly robust evidence suggesting significantand genderedchanges in parents' employment situation (e.g. Adam-Prassl et al 2020;Reichelt et al 2020).…”
Section: Introductionmentioning
confidence: 99%